Canadian International Petroleum Conference 2009
DOI: 10.2118/2009-158
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Bitumen Ultradispersed Catalytic Upgrading Experiments in a Batch Reactor

Abstract: Large reserves of heavy crude oil and bitumen are waiting for novel technical recovery developments. Nevertheless, the very low API gravity and impurities such as sulphur and nitrogen of the reserves, influences the economics of their industrial utilization. In situ catalytic upgrading of heavy oil and bitumen has been proposed and tested in laboratory scale experiments. Experimental evidence from laboratory scale tests are very promising and this novel technique can play an important role in the exploitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…On the other hand, the sequence of activation energies reported by Loria et al [14] and Martínez and Ancheyta [15] indicated that the lighter the products from hydrocracking, the higher would be the activation energy for hydrocracking reactions. The activation energies reported by Hassanzadeh and Abedi [13] showed no clear pattern. Of course, the differences in the catalyst properties, feed characteristics, experimental conditions, and the algorithms used for parameters estimation might have led to these discrepancies.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…On the other hand, the sequence of activation energies reported by Loria et al [14] and Martínez and Ancheyta [15] indicated that the lighter the products from hydrocracking, the higher would be the activation energy for hydrocracking reactions. The activation energies reported by Hassanzadeh and Abedi [13] showed no clear pattern. Of course, the differences in the catalyst properties, feed characteristics, experimental conditions, and the algorithms used for parameters estimation might have led to these discrepancies.…”
Section: Introductionmentioning
confidence: 82%
“…6 (a) Mosby et al [8] (c) Almeidaa and Guirardello [11] (b) Botchwey et al [10] (d) Sa´nchez et al [12] [12]. b Hassanzadeh and Abedi [13]. c Loria et al [14].…”
Section: Description Of the Kinetic Model And The Procedures For Parammentioning
confidence: 99%
See 2 more Smart Citations
“…To implement this process in the oil field, so as to consolidate it as a hybrid technology, different fundamental operational parameters must be analyzed, like some research works that have evaluated different parameters and their influence on the results: kind of reactor, temperature, residence time, and type of catalyst. These works use a base crude oil, with known characteristics, and carry out an experimental design capable of evaluating the sensitivity of the variables under study. As an example, for a heavy crude oil treated at 260 °C during 72 h, the viscosity reduced 46.2%, and the API gravity increased 3 units .…”
Section: Introductionmentioning
confidence: 99%